Mickiewicz u "wielkich" i "małych" Słowian (rekonesans) = Mickiewicz seen by the "great" and "minor" Slavs (reconnaissance) - Kłos, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Adam Mickiewicz was sentenced for his subversive activity into exile to Russia and arrived there in 1824. Both in Petersburg and in Moscow he met many Polish émigrés with whom he kept very close relations. He also made acquaintance and soon friendship with many anti-régime disposed Russians. Staying in Moscow, Mickiewicz was often invited to princess Volkonskaya?s palace where he became famous for his French improvisations. He was bound by ties of especial and a little bit ambivalent friendship with Alexander Pushkin. Just in Russia Mickiewicz wrote and published his Crimean Sonnets and Konrad Wallenrod. These poetic works made him known as "Slavic Byron". When Mickiewicz was leaving Russia in 1829, a company of his close Russian friends served him a farewell party. Being set free and having finally obtained his passport he headed for Germany. Going from Berlin to Dresden he must have traversed Lusatia. It is hard to guess if Mickiewicz was aware then that the Slavic minority, namely Lusatian Sorbs, still lived there. He mentioned them, especially their early history, during his lectures held at Coll?ge de France. Mickiewicz had probably no idea that the Sorbian national revival movement was being initiated just then. Sorbian national activists were inspired by the Slavic literatures, mainly Czech, Russian and Polish. The greatest Sorbian poet Jakub Bart-Ćišinski admired Mickiewicz's poetry and called him one of ?the crystal stars of Poland?. Summing up, Mickiewicz stayed in Russia for five years and published his poetic works. He was known among Sorbs of Lusatia mainly for his works. However, his poetry was highly admired both by the "great" and by the "minor" Slavs.
Keywords: Mickiewicz, Adam (1798-1855); Puszkin, Aleksander (1799-1837); literatura rosyjska; romantyzm; Łużyce; literatura łużycka; Bart-Čišinski, Jakub